Who Reconstitutes the Chemotherapy? The Educational and Practice Needs of Oncology Pharmacists in West Africa: A Call for Multidisciplinary Team Approach in Oncology Care - Runcie C.W. Chidebe; Ramatu M. Alabelewe; Krishna Prasad Sapkota; Darlingtina K. Esiaka; Candidus C. Nwakasi; Gloria C. Okwu; Jacinta Emejulu; Adamu A. Umar; Ndifreke Okwuegbunam; Funsho David; Toyosi Adepoju; Agha A. Agha; et al. (JCO Global Oncology)
PURPOSEOncology pharmacists (OPs) play a crucial role in cancer care, treatment, survivorship, and multidisciplinary teams (MDTs). OPs have specialized training in designing, administering, monitoring, and modifying oncology chemotherapy; managing adverse events; and evaluating clinical trials and investigational drugs. Yet, the state of OP has remained largely unknown in the clinical oncology workforce of the West African region. Therefore, this study aimed to understand who reconstitutes chemotherapy and to explain the OP educational and practice needs, challenges, and solutions in Nigeria.MATERIALS AND METHODSUsing a concurrent embedded mixed method design, 35 OPs completed a questionnaire, and 12 others responded to a semistructured interview. The data were then subjected to inductive thematic and descriptive analyses.RESULTSThe findings showed that 54% of the OPs were responsible for chemotherapy reconstitution, and only 60% of the oncology centers had a biosafety cabinet. 91% of OPs were practicing; however, only 54% were trained in OP, and none of the OPs were board-certified. Most of the OPs spent time weekly on reconstitution, administrative duties, teaching, and training; only 3% spent on oncology clinical trials and conferences and 8% on noninterventional research. We identified four themes: (1) Some OPs are not reconstituting chemotherapy: A Call for MDT, (2) For OP, No Training is Enough, (3) Board Certification will give OPs Recognition, and (4) Introduction of OP Course in Universities.CONCLUSIONTo improve patient treatment outcomes, training on chemotherapy reconstitution should be prioritized, integration of OPs into MDTs, and the safe handling of chemotherapy in centers should be mandated in the region. The West African Postgraduate College of Pharmacists should be supported in expanding its curriculum and introducing OP fellowships.